Optimization of ultrasound-assisted extraction, structural, functional, and antioxidant properties of Glycyrrhiza uralensis seed protein. (January 2023) - Simayi, Zelalai; Aierken, Wusimanjiang; Rozi, Parhat; Ababaikeri, Gulimire; Bo, Cao; Chenglin, Zhou; Askar, Guzalnur; Xiaojun, Yang
Abstract: The ultrasound-assisted extraction of Glycyrrhiza uralensis seed protein (GSP-U) was optimized through response surface methodology, and the enzymatic hydrolysates (GSP-H) was prepared. Then, the structural, functional properties, and antioxidant activity in vivo and in vitro were evaluated. The results showed that the optimum extraction conditions of GSP-U were as follows: ultrasonic power 400 W, time 40 min, material-liquid ratio 1:29 g/mL. Under these conditions, the yield and content of GSP-U were 15.14% and 39.72%, respectively. Alkaline protease was determined to be has a better effect on enzymatic hydrolysis of GSP-U, both GSP-U and GSP-H has great water and oil holding capacity. Additionally, GSP-H showed stronger scavenging activity on DPPH, OH and ABTS radicals, with IC50 of 0.129, 0.597 and 0.046 mg/mL, respectively. GSP-H protected mice from D -galactose-induced oxidative damage by reducing malondialdehyde (MDA) content, increasing superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) activity, and total antioxidant capacity (T-AOC) levels. This study could provide a basis for the discovery of potential development and application value of Glycyrrhiza uralensis  seed protein in the functional food, pharmaceutical, and other fields. Graphical Abstract: ga1 Highlights: The extraction process of Glycyrrhiza uralensis seed protein (GSP-U) was optimized. Four proteases were employed to hydrolyze GSP-U. GSP-U and its alcalase hydrolysate (GSP-H) showed excellent functional properties. GSP-H has strong antioxidant activity in vitro and in vivo.